2019
DOI: 10.1186/s12917-019-1781-4
|View full text |Cite
|
Sign up to set email alerts
|

The unfolded protein response induced by Tembusu virus infection

Abstract: BackgroundTembusu virus (TMUV), classified in the genus Flavivirus, causes reduced egg production and neurological problems in poultry. Flavivirus replication depends on the host endoplasmic reticulum (ER) and induces ER stress that leads to activation of the cellular unfolded protein response (UPR), an important signalling pathway that regulates many biological functions involved in viral pathogenesis and innate immunity. However, the mechanism of TMUV-induced UPR activation remains unclear.ResultsIn this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…An excessive folding activity is then prone to induce an ER stress in the infected cells and lead to apoptosis in the face of an impossible return to normality. The activation of the apoptosis promoting transcription factor CHOP during UPR is then emerging as a general response to ER-tropic viruses, replicating in the ER [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…An excessive folding activity is then prone to induce an ER stress in the infected cells and lead to apoptosis in the face of an impossible return to normality. The activation of the apoptosis promoting transcription factor CHOP during UPR is then emerging as a general response to ER-tropic viruses, replicating in the ER [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccinations [70][71][72] Microbial or virus challenges [73][74][75][76][77][78] Gut dis-bacteriosis [79][80][81][82][83] Pipping and hatching [5,84,85] A growing body of evidence clearly indicates that oxidative stress is involved in most of commercially relevant stresses in poultry production (for review see [1,2,15,60,86]).…”
Section: Internal Stressorsmentioning
confidence: 99%
“…Then we evaluated the effect of SiNPs on UPR related proteins to explore the role of UPR in apoptosis induced by SiNPs by Western blot. When cells are stimulated, PERK is first isolated from GRP78 and activated to phosphorylate eIF2α at serine residue, thus preventing protein synthesis by inhibiting mRNA translation 44 . Mechanism study showed that SiNPs block the binding of GRP78 and PERK, activate eIF2α phosphorylation, and promote the downstream signal transduction to weaken or terminate when the ER emergency continues or is serious 45 .…”
Section: Discussionmentioning
confidence: 99%
“…When cells are stimulated, PERK is first isolated from GRP78 and activated to phosphorylate eIF2α at serine residue, thus preventing protein synthesis by inhibiting mRNA translation. 44 Mechanism study showed that SiNPs block the binding of GRP78 and PERK, activate eIF2α phosphorylation, and promote the downstream signal transduction to weaken or terminate when the ER emergency continues or is serious. 45 Phosphorylated eIF2α is no longer able to associate with the translation initiation complex, leading to decreased global protein synthesis, which in turn, stimulates the expression of C/EBPhomologous protein (CHOP), causing apoptosis.…”
Section: Discussionmentioning
confidence: 99%